DESENVOLVIMENTO DE UMA FAMÍLIA DE SISTEMAS DE RECOMENDAÇÕES BASEADOS NA TECNOLOGIA DA WEB SEMÂNTICA E SEU REUSO NA RECOMENDAÇÃO DE INSTRUMENTOS JURÍDICO-TRIBUTÁRIOS - Mariano, Roberval Gomes (2008)
The huge amount of data available on the Web and its dynamic nature create a demand for information filtering applications such as recommender systems. The lack of semantic structure of data available on the Web constitutes a barrier for increasing the effectiveness of such applications family. This work discusses the analysis, design, implementation and evaluation of Semantic Web based hybrid filtering agents. Such agents were integrated in ONTOSERS, an application family for the development of recommender systems based on the Semantic Web technology. The implemented agents were evaluated and their results were compared with the results of collaborative and content-based filtering agents. The hybrid filtering techniques presented better results than the other approaches in the conducted experiments. The tested hybrid filtering approaches were the weighted and switched ones. The explicit feedback was used to validate the recommendations, presenting a better correlation with the hybrid filtering techniques. The developed agents were also evaluated through the reuse of the ONTOSERS systems family, a multi-agent recommender system in the Brazilian tributary domain.